Current global trends of aviation insurance - Ionut Valentin LOM (INCAS Bulletin, 2022)
Aviation insurance represents a special form of activity related to providing financial protection for companies operating in the aviation field. Aviation insurance is intended for the aerospace industry to cover the risks associated with its activities. It provides general liability coverage for air transport of passengers and cargo; losses caused by military operations or terrorist activities; physical damage; and liability to passengers and third parties. The recent changes in the global market situation, influenced by a complex of factors, determine the general development of aviation insurance. On the other hand, rising costs in aviation insurance and limiting the activities of service providers may hinder market growth in the medium term.